PENDEKATAN FEMINIS TERHADAP PENAFSIRAN AL-QURâAN DAN BIBEL - sabhamis, Sabhamis (AT-TALIM, 2012)
The discussion on the feminism approach to interprete Alqurâan and Bible attempts to discover verses that state about gender meanstream. Basically, the verses on gender mention that there are difference between man and woman biologically. This difference aims to make man and woman is able to complete each other so that they are able to live together peacefull and, lovely. However, dignity value between man and woman is the same. The distinction among human beings is seen from the quality of their obedience but it can not be viewed from their gender. Thus, religion rejects all type of gender descriminations.